Glomerulonefritis aguda. Estudio clínico radiológico. - Reyes Vega, Benigno J.; Peña Álvarez, Julio J.; Sánchez Vilella, Georgina (Revista Cubana de Pediatría, 2023)
Revisión de 48 casos de glomerulonefritis aguda ingresados.